Shallow submarine seep of abiotic methane from serpentinized peridotite off the Island of Elba, Italy. (January 2019) - Sciarra, Alessandra; Saroni, Anna; Etiope, Giuseppe; Coltorti, Massimo; Mazzarini, Francesco; Lott, Christian; Grassa, Fausto; Italiano, Francesco
Abstract: Abiotic methane (CH4 ) is today widely reported in gas seeps and hyperalkaline springs in ophiolites and peridotite massifs characterized by low temperature continental serpentinization. Origin and distribution of this gas have far reaching implications in microbiology, astrobiology and carbon cycle. We report an in-depth study of a recently described abiotic CH4 seep occurring in shallow seafloor along the western coast of Elba Island, Tyrrhenian Sea (Italy). The gas is characterized by stable C and H isotopic compositions of CH4 (δ 13 C ∼ −18‰; δ 2 H ∼ −141‰) and a very low CO2 content that are typical of abiotic gas in continental ultramafic rock systems. Based on local geothermal gradients, the temperature of methane production is estimated to be below 100 °C. The isotope signature of methane is similar to that occurring in the Liguria region, about 200 km north of Elba Island, where the same ophiolite unit exposed. A mantle CO2 component, suggested by relatively high 3 He/ 4 He ratios, has likely acted as CH4 precursor. The reconstruction of the geological-structural setting of Elba ophiolite sequence highlighted that the seep occurs in correspondence with a faulted reverse limb of the antiform of the ophiolite unit. The gas bearing fault forms a contact between mafic and ultramafic serpentinized rocks, as typically observed in other continental seeps and springs related to ophiolites. Magmatic intrusions in the island may have contributed to the C feedstock of methane. Highlights: Shallow seafloor gas seep related to serpentinization of Elba Island ophiolite. Geothermal gradients suggest abiotic methane production below 100 °C. Gas migrating along a tectonic contact between mafic and ultramafic rocks. Mantle carbon compound(s) as CH4 precursor(s).